Surface Roughness, Wettability and Bond Strength of Three Different Dental Repair Systems - Külünk, T.; Şinasi Sarac, Y. (Maney Publishing, 2011)
The development of fibre reinforced composite materials and technologies and the improvement strength of all-ceramics with the introduction of reinforced ceramic core materials of different compositions offer minimally invasive and increased esthetic clinical alternatives for various kinds of fixed partial restorations. Fracture of composite veneers in fibre reinforced composites or chipping of all-ceramic restorations may cause the loss of the restoration unless a reliable intraoral repair method can be provided. The purpose of the present study was to evaluate the effect of three commercially available repair kits on repair bond strength, surface roughness and wettability on all-ceramic and fibre reinforced composite materials. © W. S. Maney & Son Ltd. 2011.
Keywords: Acid Etching; Dental Adhesives; Dental Materials; Dental Restoration Failure